Valvulopathies of Rheumatic Origin: Management and Complications (London Journal of Medical and Health Research, 2024)
Objective: The objective of this study is to gather information and studies about valvular heart disease of rheumatic origin and its clinical repercussions, management and complications. Methods: Integrative review, carried out between August 2024, using the digital library Scientific Electronic Library Online (SciELO), the Virtual Health Library (VHL) and PUBMED in the databases using the Boolean operators: AND and OR. The results were obtained through management with the Rayyan 16 QCRI application and were structured in PRISMA flowcharts. Results: With the search in the databases, 219 articles were found, of which 122 were selected for reading and, according to the objective of the present work, 7 articles were included in the research. Conclusion: In the studies observed, it is concluded that rheumatic valvular disease is a high-impact condition on the quality of life of patients who suffer from them and who influence in one way or another in the development of a country, as many manifest themselves in ages at which the person is economically active and the onset and exacerbations of symptoms translate into frequent work incapacity, hospitalizations and even more so if a surgical intervention is planned. It is important that the identification of clinical patterns by health professionals, with the early diagnosis and timely treatment.
Keywords: orthodontic treatment.; cytotoxicity; oxydative stress; catalase; SOD; fixed appliances; Osteomyelitis; sinusitis; intracranial complications; epidural abscess; subdural abscess; Potts' tumor; technology; Blockchain; healthcare; U.S healthcare industry; valvulopathies; rheumatic heart disease; diagnosis; complications.